Interference of the Bugis Language in the Construction of Indonesian Language Usage - Nurlaelah Mahmud (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study titled Bugis Language Interference in the Construction of Indonesian Language Usage. Given the importance of an effective communication process in language learning, we still often encounter language errors in Indonesian interactions between students in the academic sphere. This is caused by students' bilingual ability, which is influenced using the first language or mother tongue. This study aims to describe Bugis language interference that affects the use of Indonesian. The study method used descriptive qualitative. Data were collected through direct dialog with students with recording and note-taking techniques through observation during the learning process. The results showed that students of Indonesian Language Education Study Program in Universitas Muhammadiyah Sidenreng Rappang tended to mix Bugis language when communicating using Indonesian, even in formal situations.